1970
DOI: 10.3329/bjsir.v46i1.8102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture, Water Activity and Packaging Materials on Quality and Shelf Life of Some Locally Packed Chanachur

Abstract: Five different brands of locally produced chanachur packets were collected from the market. From each brand, packets of chanachur having the same date of production were bought and stored at ambient condition (30 oC and 60 % RH) for 3 months. The changes in water activity, moisture % and consequent effect on sensory qualities like texture, color, flavor and overall acceptance were investigated every month starting from zero month. Test of packaging materials were also carried out for each brand of packed chana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…This result indicates that the water content of sausages packaged by synthetic plastic is higher than sausages packaged by BC film, thus causing microbial growth in sausages packaged in synthetic plastics, which is also higher than sausages packaged by BC film ( Figure 5 e). These results are similar to those obtained by Chowdury et al [ 49 ], who reported that the water content in food affects the weight of the food, and that water activity affects microbial growth in food. Martins et al [ 50 ] also reported that the high water content in food will trigger microbial growth.…”
Section: Resultssupporting
confidence: 91%
“…This result indicates that the water content of sausages packaged by synthetic plastic is higher than sausages packaged by BC film, thus causing microbial growth in sausages packaged in synthetic plastics, which is also higher than sausages packaged by BC film ( Figure 5 e). These results are similar to those obtained by Chowdury et al [ 49 ], who reported that the water content in food affects the weight of the food, and that water activity affects microbial growth in food. Martins et al [ 50 ] also reported that the high water content in food will trigger microbial growth.…”
Section: Resultssupporting
confidence: 91%
“…Compared with the mean rank of other attributes, the panellists were still satisfied with the colour of the stored noodles. of storage (Chowdhury et al, 2011). Other than that, the mean rank of texture attribute was 66.50 at the end of the accelerated shelf life study with the decreasing trend along the storage period.…”
Section:  Sensory Evaluation: Paired T-testmentioning
confidence: 87%
“…The sharp increase of water activity may be related to the appreciably increase in the moisture content. F3 contains considerably high fat and it leads to the rapid moisture absorption from the environment (Chowdhury et al, 2011). Figure 3, the decreasing trend of pH can be seen from 6.28 to 5.82 with significant difference (p<0.05) for almost every two months.…”
Section:  Water Activity Of Stored Instant Noodlesmentioning
confidence: 88%
“…This may have led to a degradation of the pigment and a change of color at the end of storage may be the presence of moisture may lead to increase the microbial growth, which helps the decomposition of the pigment and speed of corruption. (Chowdhury, et al, 2011) And on the other hand, this package is transparent, which helps the consumer to see the product inside and at the same time leads to the sweets being exposed to strong light, which negatively affects the color fastness in the candy for a long time, which led to the deterioration of the color at the end of the storage period. Because this type of packaging is transparent, it allows the transmission of light, which plays a role in the deterioration of the color.…”
Section: Figure 5 Effect Of Polyester (Pet) Package On the Stability ...mentioning
confidence: 99%